“Inclusión de harina de fréjol de palo (Cajanus cajan) en la dieta sobre los parámetros productivos y la calidad de la carne de (Andinoacara rivulatus)” - Ruis Torres, Carmen Mercedes (2021)
The objective was to evaluate the influence of inclusion of wood bean flour (Cajanus cajan) as a food source for aquaculture exploitation, in old blue (Andinoacara rivulatus) in the final phase in an intensive controlled captivity system; It was carried out in the Buena Fe canton, 16 km from the Federico Intriago Precinct owned by Mr. Alfonso Benavides, located on the Santo Domingo-Quevedo road. 3 levels of wood bean flour were evaluated (T0: 0%; T1: 10%; T2: 15%; T3: 20%); 128 units of 80 grams were used in an Andinaocara juvenile stage, arranged in cages. Different behaviors were obtained in all the treatments in each measured variable (P <0.05) and showed significant differences between treatments; The final results for T1 with the inclusion of 10% of bean flour had the highest values in weight gain and a higher survival rate throughout the experiment, while T2 and T3 had mortality from the first week, Possibly due to the tannin factor, the fillet yield of T1 was 57.18%, the carcass yield was 94.59%, presenting the best responses and the by-product yield of 42.82%. While with the commercial balance it was well below 51.99 fillet 93.33 carcass and the by-products 99.97 who was on par was the T2 but when incorporating the 20% inclusion of flour, survival decreased. It is recommended to use Canajus cajan provides 32% of dry protein, obtaining very good results from its increase in weight gain .Using Canajus cajan is very beneficial since it is a legume that in our study of nutritional quality provided us with 32% dry protein, of course the protein varies with tender but still being a protein food, it has a great advantage that contributes to the nutrition of the species in small quantities that therefore we have very good results from its increase in weight gain. All the treatments had different behaviors in each of the measured variables (P <0.05) and showed a significant difference between treatments. In addition, it was possible to increase a very effective premix to increase the consumption of the species, the legume being very suitable for a premix with the balanced in its diet, providing very effective nutrition. Keywords: Diet, native fish, quality, intensive, analysis, extraction.